2015
DOI: 10.4103/0366-6999.168044
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Mobile-bearing Unicompartmental Knee Arthroplasty

Abstract: Background:Controversies about the rational positioning of the tibial component in unicompartmental knee arthroplasty (UKA) still exist. Previous finite element (FE) studies were rare, and the results varied. This FE study aimed to analyze the influence of the tibial component coronal alignment on knee biomechanics in mobile-bearing UKA and find a ration range of inclination angles.Methods:A three-dimensional FE model of the intact knee was constructed from image data of one normal subject. A 1000 N compressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 32 publications
3
48
0
Order By: Relevance
“…On the other hand, Sawatari et al 11 and Iesaka et al 12 reported that valgus alignment is preferable to get a satisfactory stress distribution using analysis of subchondral bone under the tibial component. Zhu et al 13 reported that the middle position is best. Thus, the optimal alignment of the tibial implant in UKA is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Sawatari et al 11 and Iesaka et al 12 reported that valgus alignment is preferable to get a satisfactory stress distribution using analysis of subchondral bone under the tibial component. Zhu et al 13 reported that the middle position is best. Thus, the optimal alignment of the tibial implant in UKA is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have focused not only on stress or strain on bone, but also looked at stress on soft tissue. Therefore, modeling not only of the femur, but also of cartilage and the lateral meniscus became required (Innocenti et al, 2014;Innocenti et al, 2016;Kang et al, 2018f;Kang et al, 2019c;Kang et al, 2018h;Kang et al, 2018i;Kang et al, 2018j;Kwon et al, 2014;Kwon et al, 2017;Park et al, 2019;Simpson, Price, Gulati, Murray and Gill, 2009;Wen et al, 2017;Zhu et al, 2015).…”
Section: Application Of Computational Simulation In Pre-or Post-clinimentioning
confidence: 99%
“… 7 - 9 While previous biomechanical studies have shown that resection depth, component rotation and sagittal and coronal alignment of the tibial component can significantly affect proximal tibial strain after medial UKA, we are unaware of any published studies that evaluate the effect of implant position on tibial strain after lateral UKA. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%